2004
DOI: 10.4049/jimmunol.172.3.1380
|View full text |Cite
|
Sign up to set email alerts
|

Tc1 and Tc2 Effector Cell Therapy Elicit Long-Term Tumor Immunity by Contrasting Mechanisms That Result in Complementary Endogenous Type 1 Antitumor Responses

Abstract: Cytolytic CD8+ effector cells fall into two subpopulations based on cytokine secretion. Type 1 CD8+ T cells (Tc1) secrete IFN-γ, whereas type 2 CD8+ T cells (Tc2) secrete IL-4 and IL-5. Both effector cell subpopulations display predominantly perforin-dependent cytolysis in vitro. Using an OVA-transfected B16 lung metastases model, we show that adoptively transferred OVA-specific Tc1 and Tc2 cells induce considerable suppression, but not cure, of pulmonary metastases. However, long-term tumor immunity prolonged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 67 publications
3
44
0
1
Order By: Relevance
“…Recently, it has been reported that membrane TNF-a can delay T-cell activation-induced cell death by activation of AKT and NF-kB, 64 which leads to elongated T-cell survival. Our results are thus consistent with a previous report by Dobrazanski, et al, 65 demonstrating that CD8 þ T-cell therapeutic effect was significantly less efficient in TNF-a À/À KO mice. These long-lived memory T cells possess the unique ability to respond rapidly and specifically to the antigen.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Recently, it has been reported that membrane TNF-a can delay T-cell activation-induced cell death by activation of AKT and NF-kB, 64 which leads to elongated T-cell survival. Our results are thus consistent with a previous report by Dobrazanski, et al, 65 demonstrating that CD8 þ T-cell therapeutic effect was significantly less efficient in TNF-a À/À KO mice. These long-lived memory T cells possess the unique ability to respond rapidly and specifically to the antigen.…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, our data also demonstrated that transfer of the engineered CD8 þ T TNF cells further leads to a stronger longterm antitumor immunity against the IL-10-secreting B16 OVA/ILÀ10 tumor cell challenge. Dobrazanski et al 65 previously reported the induction of the host antigen-specific CD8 þ Tm cells in lung tissues after adoptive transfer of the donor antigen-specific CD8 þ effector T cells. However, the mechanism involved in this interesting finding was not elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…ϩ Tc-derived Tm cells (46,47). However, the corresponding immune mechanism behind this finding has not been disclosed.…”
Section: Discussionmentioning
confidence: 85%
“…For some studies, we used B16 tumors that express the model tumor Ag OVA [B16-OVA; kindly provided by R.W. Dutton, Trudeau Institute (16)]. To establish tumors in mice, 0.5 3 10 6 to 1 3 10 6 tumor cells in 50 ml PBS were injected s.c. into the flank or i.v.…”
Section: Tumor Modelsmentioning
confidence: 99%